Approaching Green BPM characterisation. Issue 2 (5th November 2018) - Hernández González, Anaisa; Calero, Coral; Pérez Parra, Dianelys; Mancebo, Javier
Abstract: Sustainable development is a type of development that meets the needs of the present without compromising the ability of future generations to meet their own needs. Sustainability has recently become more and more important for businesses. This has led to what is known as Green BPM (Green business process management), in which sustainability is considered to be a business objective. The objective of this work was to carry out a systematic literature review in order to evaluate how the subject of Green BPM has evolved and how the term "Green BPM" has been conceptualised so as to propose a new definition compiled from those previously formulated; identify the impact of the incorporation of Green aspects into the BPM life cycle stages; and discover the impact of Green BPM research efforts by means of the PDCA (plan‐do‐check‐act) model, thus identifying (1) the goals that have been proposed when Green initiatives are carried out in BPM, (2) the context in which this has been applied, and (3) the performance indicators considered. Finally, we propose a new characteristic, Process Greenability, together with its subcharacteristics, in addition to identifying the relationship between these subcharacteristics and the indicators identified to make them measurable.